The Framework for Responsible Research With Australian Native Plant Foods: A Food Chemist's Perspective - Fyfe, Selina; Smyth, Heather E.; Schirra, Horst Joachim; Rychlik, Michael; Sultanbawa, Yasmina (Frontiers in Nutrition, 2022)
Australia is a rich source of biodiverse native plants that are mostly unstudied by western food science despite many of them being ethnofoods of Australian Indigenous people. Finding and understanding the relevant policy and legal requirements to scientifically assess these plants in a responsible way is a major challenge for food scientists. This work aims to give an overview of what the legal and policy framework is specifically related to food chemistry on Australian native plant foods, to clarify the relationships between the guidelines, laws, policies and ethics and to discuss some of the challenges they present in food chemistry. This work provides the framework of Indigenous rights, international treaties, federal and state laws and ethical guidelines including key legislation and guidelines. It discusses the specific areas that are applicable to food chemistry: the collection of plant foods, the analysis of the samples and working with Indigenous communities. This brief perspective presents a framework that can be utilised by food chemists when developing responsible research involving plant foods native to northern Australia and can help them understand some of the complexity of working in this research area.